50 знаменитых городов мира - Скляренко Валентина Марковна (100 знаменитых, 2005)
Экземпляры: КХ (20060809) / Инвентарный номер: 1058903 / Цена: 138.05 / Сис.шифр: 63.3(0) / Авт.знак: П 99 / ГРНТИ: 03 / ББК: 63.3(0)